The determinants of hedging with derivatives by non-financial firms in China - Xie, Muliang (2020)
This paper tries to explore the determinants of hedging with derivatives by non-financial firms in China in which the derivatives markets appear late but develop rapidly. On the basis of previous research, some hedging hypotheses are mentioned from many aspects including corporate tax convexity, cost of financial distress, economies of scale, underinvestment, liquidity and foreign exchange exposure hypothesis. The sample is obtained from the CSMAR database and annual reports and consists of financial data from non-financial firms in the CSI 300 index, which could be representative of the Chinese domestic market. This study applies the combination of univariate and multivariate logistic regression, with some other tests such as the test of difference and multicollinearity test. The results of this study are that consistent with the economies of scale, the firm size is the most important determinant that positively induces non-financial firms to hedge with derivatives. Following the economies of scale, liquidity also plays an important role in driving non-financial firms to use derivatives for hedging purposes, which is in line with the hedging hypothesis of liquidity.